(untitled) (Clinics, 2021)
OBJECTIVES: To investigate the role of miR-139-5p and the TLR4/MyD88/NF-kB signaling pathway in acute lung injury in septic mice. METHOD: A total of 140 healthy male SPF C57BL/6 mice were divided into seven groups, i.e., Normal, Control, NC, miR-139-5p mimic, miR-139-5p inhibitor, TAK-242, and miR-139-5p inhibitor+TAK-242 groups. The levels of miR-139-5p, proteins related to the TLR4/MyD88/NF-kB signaling pathway (TLR4, MyD88, and p-NF-kB p50), and MPO, SOD, GSH, and MDA in lung tissue were measured. The lung tissue wet-to-dry mass ratio (W/D), arterial oxygen partial pressure (PaO2), and carbon dioxide partial pressure (PaCO2) were measured. RESULTS: A web-based bioinformatic tool predicted that MyD88 was a target of miR-139-5p, which was verified by a dual luciferase reporter assay. Compared with those in the Normal group, the levels of miR-139-5p, PaO2, SOD, and GSH were significantly lower, while those of TLR4, MyD88, p-NF-kB p50, W/D, PaCO2, IL-1b, TNF-a, IL-6, MPO, and MDA were higher in all other groups. Moreover, compared with their levels in the Control group, these indicators exhibited contrasting results in the miR-139-5p mimic and TAK-242 groups, but were similar in the miR-139-5p inhibitor group. In the miR-139-5p inhibitor+TAK-242 group, acute lung injury, aggravated by miR-139-5p inhibitor, was partially rescued by TAK-242. CONCLUSION: miR-139-5p inhibits the TLR4/MyD88/NF-kB signaling pathway to alleviate acute lung injury in septic mice.